Reproductive modes in frogs and their unexpected diversity in the Atlantic forest of Brazil - Haddad, Célio F. B. [UNESP]; Prado, Cynthia P. A. [UNESP] (Oxford University Press (OUP), 2005)
Amphibians, and especially the anurans (frogs and toads), exhibit a greater diversity of reproductive modes than other tetrapod vertebrates. Twenty-nine reproductive modes have been recognized for the anurans; we propose 10 more, elevating by more than 34% the number of reproductive modes known for anurans worldwide. These newly recognized reproductive modes for the frogs elevate by almost 48% the number of anuran reproductive modes known for the Neotropics. The highly complex topography of the Atlantic forest, breaking up the biome into many small microhabitats, and the high humidity, which reduces desiccation risks, have enabled the evolution of reproductive specializations such as eggs or tadpoles that develop out of water. Nearly 90% of the Atlantic forest has been cleared, and because several anurans are endemic to this region or have specialized reproductive modes dependent on the forest, this partly explains the generalized population declines and large numbers of species that have disappeared in the last few decades. © 2005 American Institute of Biological Sciences.
Keywords: Amphibia; Anurans; Atlantic forest; Conservation; Reproductive modes; Anura; Tetrapoda; Vertebrata